Analisis Jumlah Pelanggan Listrik Terhadap Penerimaan Pajak Penerangan Jalan Di Kabupaten Buleleng - Saputra, I Ketut Triadi; Diatmika, I Putu Gede (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
Street Lighting Tax (PPJ) is an important part of local taxes related to the number of electricity customers in Buleleng Regency, the PPJ includes regional levies by industrial and non-industrial use of electricity. The purpose of this study was to determine how the attachment of electricity customers to a street lighting tax revenue. This research observation took place in stages by examining the data obtained from PT PLN (Persero) UP3 North Bali. Documents and evidence collected in this study were from street lighting tax data, data on the realization of depositing the results of PPJ billing, as well as data on collective billing from the Buleleng Regency Government PJU. The data period used is December 2021. The results of the study show that the total amount of PPJ levy receipts in 2021 is Rp. 39,098,218,805 have been deposited with the Buleleng Regency Government, and the total collective bill of the Buleleng Regional Government PJU in 2021 is Rp. 15,983,776,581. The result total between realization of PPJ receipts and the total collective billing of the Regional Government PJU, the PPJ contribution received by the Regional Government as PAD is Rp. 23,114,442,224. From the results of the data research, it is known that the number of electricity customers will have an impact on the PPJ that will be received by the Regional Government as PAD in Buleleng Regency.